2015
DOI: 10.1371/journal.pone.0120852
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Five Driver Gene Mutations in Patients with Treatment-Naïve Lung Adenocarcinoma in Taiwan

Abstract: BackgroundIt is important to select appropriate targeted therapies for subgroups of patients with lung adenocarcinoma who have specific gene alterations.MethodsThis prospective study was a multicenter project conducted in Taiwan for assessment of lung adenocarcinoma genetic tests. Five oncogenic drivers, including EGFR, KRAS, BRAF, HER2 and EML4-ALK fusion mutations, were tested. EGFR, KRAS, BRAF and HER2 mutations were assessed by MALDI-TOF MS (Cohort 1). EML4-ALK translocation was tested by Ventana method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 41 publications
4
126
4
Order By: Relevance
“…Such distinct response to gefitinib suggested that LTS group in our study is very likely a group of EGFR-mutant lung adenocarcinoma. Anaplastic lymphoma kinase (ALK) fusion oncogene is an emerging molecular target in lung adenocarcinoma (30), which accounts for 3-5% of genetic alteration (12,31,32). Patients with ALK fusion oncogene were characterized by younger age, non-smoking status and good response to several TKIs (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such distinct response to gefitinib suggested that LTS group in our study is very likely a group of EGFR-mutant lung adenocarcinoma. Anaplastic lymphoma kinase (ALK) fusion oncogene is an emerging molecular target in lung adenocarcinoma (30), which accounts for 3-5% of genetic alteration (12,31,32). Patients with ALK fusion oncogene were characterized by younger age, non-smoking status and good response to several TKIs (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with advanced NSCLC harboring oncogenic driver mutation had better survival outcome as comparing to patients without driver mutation (10,11). In Asia-Pacific region, EGFR exon 18-21 mutation is the most common type of oncogenic mutation in lung adenocarcinoma, with incidence rate of 55% (12). Tyrosine kinase inhibitors (TKIs) targeting EGFR had been shown to improve progression-free survival in patients with advanced NSCLC harboring sensitive EGFR mutation status in first line setting (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…BRAF p.V600E mutation is more frequent in females 52,54 and never smokers 54 in some studies, but several studies failed to show these associations. 49,50,53,58 One distinction between BRAF mutations and other Figure 1 Forest plot of sensitivity and specificity for immunohistochemistry (IHC)-based determination of ROS1 rearrangement positivity compared with fluorescence in situ hybridization. Pooled estimate of sensitivity and specificity based on bivariate analysis of included studies.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…FN, false-negative; FP, false-positive; TN, true-negative; TP, true-positive. jmd.amjpathol.org -The Journal of Molecular Diagnostics targetable oncogenes is that non-p.V600E BRAF mutations (particularly the exon 11 mutations) may coexist with mutations in KRAS, 49,52,53,59 whereas the p.V600E mutations are mutually exclusive of KRAS, EGFR, or ALK alterations.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
See 1 more Smart Citation